Cost minimization of 3 methods of acquiring dental radiographic image. (30th September 2020) - Coscarelli, C; Leoni, L; Força, F; Feris, F; Nacao, N; Fonseca, F; Machado, M; Raimundo, R; Cavalcante, C; Pereira, P
Abstract: The objective of this study is to develop a complete economic evaluation of 3 diagnostic techniques for interproximal radiographic, comparing the conventional radiographic technique, direct (CMOS) and indirect (PSP) digital techniques in the diagnosis of dental caries, from the perspective of SESC/Brazil (Social Trade Service). A complete cost-minimization economic assessment was performed. Initially, a systematic review was performed and it was verified that the accuracy for the diagnosis is similar between the techniques. The direct medical costs (related to the technique) were estimated by the bottom-up technique, taking into account the value of the clinical hours of the professionals, equipments and materials used. The time horizon was 10 years. The values were discounted at 3% per year, and a sensitivity analysis was prepared into two scenarios (one more pessimistic with costs 20% higher than estimated and one more optimistic with costs 20% lower). Direct digital radiography proved to be the option with the lowest cost (US 1.16), followed by semi-direct (US 1.35) and conventional (US 1.47). Conventional radiography presented the highest cost for the period (US 74, 943.65), and the use of digital radiographs could promote savings of US 6, 000.59 and US 15, 448.35, if used by the semi-direct and direct method. respectively. Regarding the sensitivity analysis, in the most optimistic scenario of the time horizon there would be savings of US 4, 800.47 (semi-direct digital) to US 12, 446.09 (direct digital) compared to the traditional technique (films). In the most pessimistic scenario, these values vary in savings over the time horizon from US 7, 200.71 (semi-direct) to US 18, 538.02 (direct). It is concluded that the direct radiographic technique was the most cost effective and its incorporation in the SESC units is suggested. Key messages: Digital dental radiography. Cost minimization analysis. Health technology assessment.